Artificial Look: Body Narcissism in the Fashion and Cosmetic Industry - Sigdel, Sangita (Journal of Productive Discourse, 2024)
Consumers universally engage with cosmetic products in pursuit of bodily perfection, often influenced by prevailing fashion trends dictating societal beauty standards through advertising. Consequently, a woman's body serves as a cornerstone of identity, its alignment with these standards transforming it into a commodified entity. While the fashion industry ostensibly champions feminist ideals of empowerment, its underlying motive remains profit generation. This paper endeavors to explore the commodification of women's bodies within the fashion and cosmetic industries, illuminating its enduring implications. Through a historical analysis spanning from the colonial era to contemporary society, we examine the evolution of the body as a commodity, drawing on secondary sources and available data on beauty standards. Grounded in Saussure's structuralist framework, this study aims to unravel the intricate dynamics underpinning the commodification process and its broader societal ramifications.